The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0103-97332004000400034
|View full text |Cite
|
Sign up to set email alerts
|

A new route for preparing CdS thin films by chemical bath deposition using EDTA as ligand

Abstract: Progress is reported towards the development of a new route to obtain cadmium sulfide (CdS) thin films by using ethylene-diamine-tetra-acetic acid (EDTA) ligand on the chemical bath deposition (CBD) method. Different chemical baths are used to study changes in the structures of the CdS films for different EDTA concentrations. X-ray diffraction (XRD) is used to prove the structural characterization of the samples, and to obtain the grain size with the Scherrer's equation. The pH variations during the growth als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 6 publications
4
22
0
Order By: Relevance
“…Only anatase phase was observed in both samples. The crystal sizes (L c ) of TiO 2 before and after heat treatment were calculated using Scherrer's equation [23]: Absorbance (-)…”
Section: Resultsmentioning
confidence: 99%
“…Only anatase phase was observed in both samples. The crystal sizes (L c ) of TiO 2 before and after heat treatment were calculated using Scherrer's equation [23]: Absorbance (-)…”
Section: Resultsmentioning
confidence: 99%
“…The maximum carrier concentration value is 1.986 9 10 20 cm -3 for 250°C. However, further increase of substrate temperature reduced the carrier [28]. Figure 9 shows the variation of gas response at 600 K with different gas concentrations.…”
Section: Electrical Studiesmentioning
confidence: 99%
“…It is a direct band gap material and one of the most useful semiconductor materials with its wide range of applications in semiconductor devices such as fabrication of solar cells as optical windows [2], piezo-electronic and optoelectronic [3] devices such as thin film optical integrated circuits. CdS thin films are also useful in electronic devices such as field effect transistor [2], light emitting diodes [4]. In the case of thin film solar cells, it has been reported that efficient thin film solar cells are obtained using CdS as an n-partner.…”
Section: Introductionmentioning
confidence: 99%